Zakat Fundraising Via Instagram: How Does It Advantageous for Zakat Institutions? - Pusparini, Martini Dwi; Bapang, Siti Hanifah; Virgiawan, Rheyza (Journal of Contemporary Applied Islamic Philanthropy, 2023)
Purpose: The digital transformation of zakat institutions emerges as a crucial concern. The aim of this research is to analyze the impact of Instagram social media marketing on fundraising in BAZNAS Kota Yogyakarta. Methodology: This research adopts a descriptive qualitative methodology in conjunction with content analysis. The data was gathered by documentation and in-depth interviews to the head of fundraising, Instagram admin, and five Instagram followers. Findings: The findings indicate that Instagram is advantageous for Zakat institution to increased fund growth, a rise in the number of muzakki, building institutional image, increasing muzakki awareness, and as a means of Islamic da'wah platform to increase followers' knowledge about zakat, infaq, and shodaqoh. The positive outcomes observed at BAZNAS Kota Yogyakarta from using Instagram marketing led to the conclusion that this platform can effectively serve as a medium for collecting zakat, infaq, and shodaqoh funds for Islamic philanthropic institutions like BAZNAS.